2021
DOI: 10.3389/ijph.2021.598083
|View full text |Cite
|
Sign up to set email alerts
|

Employment Status and Health Literacy in Denmark: A Population-Based Study

Abstract: Objectives: Examining whether specific population groups who are not working and those who have an employment have the same health literacy level.Methods: Data were retrieved from a nationally representative cross-sectional study of the Danish population conducted with the health literacy questionnaire (HLS-EU-Q16) in 2016 and 2017. Socio-demographic characteristics were drawn from national registers. Odds ratio for the association between employment status and health literacy was estimated from logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
(45 reference statements)
2
9
2
1
Order By: Relevance
“…As established in previous relevant research, the higher the level of education was, the higher the level of COVID-19 VL was [ 2 , 13 , 15 , 16 ]. Employed participants had a significantly lower level of COVID-19 VL in comparison with unemployed participants, which is in opposition to previous research [ 22 ]. However, Khoshravesh et al [ 23 ] also reported about the borderline level of health literacy of employed people in Iran.…”
Section: Discussioncontrasting
confidence: 99%
“…As established in previous relevant research, the higher the level of education was, the higher the level of COVID-19 VL was [ 2 , 13 , 15 , 16 ]. Employed participants had a significantly lower level of COVID-19 VL in comparison with unemployed participants, which is in opposition to previous research [ 22 ]. However, Khoshravesh et al [ 23 ] also reported about the borderline level of health literacy of employed people in Iran.…”
Section: Discussioncontrasting
confidence: 99%
“…We observed that employment was associated with inadequate HL which contradicts the results from other studies [64][65][66] where unemployment was associated with inadequate HL. Post hoc analysis of our data showed that those who were unemployed had higher odds of multimorbidity (OR:2.63, 95% CI: 1.3-5.4, p = 0.01), after adjusting for other sociodemographic correlates.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, knowledge and compliance of medication both affected patients' decision-making behaviors, which echoes ndings from previous studies [7,10,39,40]. A positive association between medical knowledge and SDM has been established in prior researches [7,41,42]. Shen et al considered that lower health knowledge undermines patients' self-con dence during communication with their doctors, which results in patients undervaluing the information they provide to doctors [43].…”
Section: Discussionsupporting
confidence: 83%